1967
DOI: 10.2307/4083254
|View full text |Cite
|
Sign up to set email alerts
|

On the Sierra Madre Sparrow, Xenospiza baileyi, of Mexico

Abstract: THE Sierra Madre or Bailey's Sparrow, Xenospiza baileyi, was described as a new genus and species from the high mountains of Durango and Jalisco less than 35 years ago (O. Bangs, Proc. •Vew England Zool. Cl., 12: 85-88, 1931). It has since been considered rare, and even 19 years ago, when F. A. Pitelka (Condor, 49: 199-203, 1947) described a new subspecies, only 11 specimens were known, of which he had at hand only 1 from La Cima, Distrito Federal, and 3 from western Mexico. Today the population from the sacat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 0 publications
0
20
0
15
Order By: Relevance
“…As mentioned above, the UCE tree also provides insight into the origins of ecological diversity in sparrows. Grassland-dwelling sparrows, for example, do not form a clade, but instead occur in 3 phylogenetically distant clades (A, F, and G), suggesting more transitions between different habitat types (e.g., grassland, brushland, and forest) over evolutionary time than were previously suspected (e.g., Paynter 1964, Dickerman et al 1967.…”
Section: Discussionmentioning
confidence: 85%
“…As mentioned above, the UCE tree also provides insight into the origins of ecological diversity in sparrows. Grassland-dwelling sparrows, for example, do not form a clade, but instead occur in 3 phylogenetically distant clades (A, F, and G), suggesting more transitions between different habitat types (e.g., grassland, brushland, and forest) over evolutionary time than were previously suspected (e.g., Paynter 1964, Dickerman et al 1967.…”
Section: Discussionmentioning
confidence: 85%
“…Sierra Madre Sparrows ( Xenospiza baileyi ) belong to a monotypic genus of the family Emberizidae restricted to the high mountains of northwestern and central Mexico (Dickerman et al 1967), and are one of 19 Mexican bird species considered endangered (IUCN 2004, Oliveras de Ita and Gómez de Silva 2007). The first eight known specimens were obtained in 1889 in the Sierra de Bolaños, Jalisco, by W. B. Richardson, but the species was not described formally until Bangs (1931), who, with a new specimen from southcentral Durango, demonstrated that it was not a hybrid as previously supposed (Bailey and Conover 1935).…”
mentioning
confidence: 99%
“…Information on the habitat requirements of this species is scarce, and known information is based almost exclusively on the transvolcanic belt populations that appear associated strictly with bunchgrass meadows ( Festuca lugens , F. tolucensis , and Muhlenbergia quadridentata ) in pine forest (Dickerman et al 1967, Howell and Webb 1995, Cabrera‐García et al 2006). Information about northern populations is limited to simple macrohabitat descriptions (Bangs 1931, Bailey and Conover 1935) and more recent descriptions by Oliveras de Ita and Rojas‐Soto (2006).…”
mentioning
confidence: 99%
“…Two lines of evidence suggest both historical and current ecological equivalence between the populations of the Sierra Madre sparrow. First, X. baileyi populations show no differences in morphology, plumage coloration or behavior between the SMO and TVB populations (Dickerman et al 1967), leading to the species currently being considered monotypic (contrary to the earlier suggestion by Pitelka 1947, which was based on inadequate sampling). Secondly, with respect to ecological equivalence, Rojas-Soto et al (2008) concluded that the TVB and SMO populations are found in similar ecological environments based on ecological niche models.…”
Section: Delimitation Of Management Units and Management Strategymentioning
confidence: 90%
“…it requires for breeding (Oliveras de Ita and Gómez de Silva 2007), making it highly likely that the pine forests and large cultivated areas within its limited range act as barriers to the dispersal of individuals. On the basis of field observations (Oliveras de Ita and Rojas-Soto 2006), published historical records (Bangs 1931;Bailey and Conover 1935;Dickerman et al 1967), and a review of specimen collections (Navarro et al 2002), it is evident that the Sierra Madre sparrow has suffered a severe reduction in its range as a consequence of habitat destruction, which has already caused population extinctions in the states of Jalisco, Durango and México. A decade ago it was estimated that more than 50% of suitable habitat had disappeared in the previous 10 years (Cabrera 1999;González 2000), and the factors leading to this decrease have not diminished.…”
Section: Introductionmentioning
confidence: 98%